The Pattern and Function of Manchu Shamans’ Guardian Spirits (Journal for the Study of Religion and History (JSRH), 2026)
The Manchus use Amba Weceku to refer to the guardian spirits of the Amba Samans. The guardian spirits are arranged in rows, with each row consisting of one leading spirit and several helping spirits. Mastering the guardian spirits is an important criterion for examining and certifying the status of an Amba Saman. The formation of the concept of guardian spirits in shamanism not only reflects the needs at the unconscious level but also incorporates conscious construction under specific historical conditions. The fantastical construction of the guardian spirits in Manchu shamanism has a solid real social foundation. Compared with the shamanism of other Tungusic tribes, its structure places greater emphasis on “hierarchy” and “seniority”, and its content highlights “heroes and war gods”. As a symbolic system of emotional form, these guardian spirits represent different states of psychological imbalance. Shamans use their guardian spirits to dispel harmful spirits or regulate imbalances in the soul.
Keywords: Amba Saman, guardian spirits, pattern, function